Pengembangan Sistem Informasi Manajemen Gudang Pada PT. Inti Karsa Banten Menggunakan Metode Zachman Framework - Sarah Rachmi Indahsari; Yusi Tyroni Mursityo; Welly Purnomo (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Supply Chain Management (SCM) is an important part of a company engaged in industry. SCM has several main activities namely, designing products, providing raw materials, making production, and delivering goods. PT. Inti Karsa is a company engaged in industry. The items that are traded are paper and cardboard specifically for shoe products. All existing business processes are still carried out with the help of Microsoft Office Excel and Microsoft Office Word, from recording the stock out and entry of goods, and all reports are done manually without a system. The most important problem that is felt namely, the head of warehouse often makes mistakes in recording the stock of goods that come out or in. Therefore a special information system is needed to support the warehousing process of PT. Inti Karsa. The method that development of information systems uses is zachman framework method, because this method has many perspectives that can help facilitate the process of developing the required warehousing system. The perspective that used is a planner, owner / analyst, designer and builder. The results of this study is a prototype of a warehousing information system that will be developed with the help of the zachman framework method. The results of the black-box test with 37 test cases with 100% valid results, the results of user acceptance test using 2 criteria namely, usability and functional correctness and completeness with the results of the percentage system approved as much as 96.66%, and compatibility testing found that the system can be used at 9 different types of web browsers.